2016
DOI: 10.1128/jcm.03302-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Check-Points Check MDR CT103 and CT103 XL Microarray Kits by Use of Preparatory Rapid Cell Lysis

Abstract: Using a rapid bacterial lysis method, the Check MDR CT103 and CT103 XL microarrays demonstrated accuracies of 98.1% and 94.2%, respectively, for detection of known resistance genes in 108 multidrug-resistant Gram-negative bacilli. In 45 isolates, 49 previously unrecognized extended-spectrum ␤-lactamase or plasmid AmpC targets were detected and confirmed by conventional PCR. Multidrug-resistant Enterobacteriaceae (MDRE), especially those producing carbapenemases, are of concern to physicians and laboratorians w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The results of CT 103 XL microarray showed the high accuracy for the detection of β-lactamases in A. baumannii. The similar findings have been reported by Cunningham et al (2016) and Juiz et al (2014) from microarray technique for characterization of resistance mechanism in MDR Enterobacteriaceae (MDRE) and Pseudomonas aeruginosa.…”
Section: Rapid Molecular Identification Of Carbapenemase Genes Insupporting
confidence: 87%
See 1 more Smart Citation
“…The results of CT 103 XL microarray showed the high accuracy for the detection of β-lactamases in A. baumannii. The similar findings have been reported by Cunningham et al (2016) and Juiz et al (2014) from microarray technique for characterization of resistance mechanism in MDR Enterobacteriaceae (MDRE) and Pseudomonas aeruginosa.…”
Section: Rapid Molecular Identification Of Carbapenemase Genes Insupporting
confidence: 87%
“…baumannii, as well (Cunningham et al, 2016;Bogaerts et al, 2012). In this study, a novel array Check-Points carbapenemases, ESBLs and AmpCs Microarray (Check-MDR CT103XL; Check-Points B.V., Wageningen, the Netherlands) was used to detect all the previously targeted genes,…”
mentioning
confidence: 99%
“…Therefore, the new CT103XL platform showed 100% accuracy in identifying mcr-1 and mcr-2. We also noted that all bla genes were correctly identified (Table S1), thereby confirming previous validations (7,14,15).…”
supporting
confidence: 87%
“…However, recent studies have demonstrated sensitivities and specificities of 100% and accuracies of 94% for the detection of known resistance genes using the Check-Points MDR CT103 XL microarray kit (4,5).…”
Section: Discussionmentioning
confidence: 99%